2003
DOI: 10.1118/1.1534109
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional diffuse optical tomography in the parallel plane transmission geometry: Evaluation of a hybrid frequency domain/continuous wave clinical system for breast imaging

Abstract: Three-dimensional diffuse optical tomography (DOT) of breast requires large data sets for even modest resolution (1 cm). We present a hybrid DOT system that combines a limited number of frequency domain (FD) measurements with a large set of continuous wave (cw) measurements. The FD measurements are used to quantitatively determine tissue averaged absorption and scattering coefficients. The larger cw data sets (10(5) measurements) collected with a lens coupled CCD, permit 3D DOT reconstructions of a 1-liter tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
229
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(235 citation statements)
references
References 43 publications
4
229
0
2
Order By: Relevance
“…11,[15][16][17][18][19][20][21][22] To increase the number of measurement data, Culver et al reported a charge coupled device (CCD) camera based DOT imaging system. 23 Turner et al used a CCD camera to measure early photons in a DOT imaging system. 24 In this study, we used an electron multiplying CCD (EMCCD) camera to measure light intensity on the breast surface in a transmission mode.…”
Section: Introductionmentioning
confidence: 99%
“…11,[15][16][17][18][19][20][21][22] To increase the number of measurement data, Culver et al reported a charge coupled device (CCD) camera based DOT imaging system. 23 Turner et al used a CCD camera to measure early photons in a DOT imaging system. 24 In this study, we used an electron multiplying CCD (EMCCD) camera to measure light intensity on the breast surface in a transmission mode.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we focus here on the reconstruction of absorbing inhomogeneities assuming that the diffusion coefficient of the medium is constant. Reconstruction of purely absorbing inhomogeneities have been employed, for example, in breast imaging [17][18][19][20] or blood oxygenation level imaging [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The breast is slightly compressed between two parallel glass plates or plates made of other material through which light can pass [33,37,59,60]. These plates typically house optical fibers for illumination and light detection.…”
Section: Geometric Designmentioning
confidence: 99%